Biomedical Signal Acquisition of Heart Rate and SpO2 Using Arduino-Based Platform - Kazem, Fatima Mahdi sahib; Atiyah, Hasan Abdulkareem Hameed; Mahdi, Zahraa Najih Muhammad; Ghanem, Tiba Saad Muwafaq (Central Asian Journal of Medical and Natural Science, 2025)
This project presents the development of a portable system for real-time monitoring of heart rate and blood oxygen saturation (SpO₂) using Arduino technology. The device utilizes a pulse sensor and integrates a MAX30100 optical sensor to collect biometric data in a non-invasive manner. Traditional methods of monitoring vital signs—such as checking the pulse manually or using standard hospital equipment—are often limited by accessibility, cost, or complexity. In contrast, this Arduino-based system provides a low-cost and user-friendly alternative that can be used in various environments including homes, schools, and clinics. The system measures heartbeat and SpO₂ levels using photoplethysmography (PPG) and displays the results on an LCD screen. This study explores the design, hardware implementation, and operational testing of the system, demonstrating its potential as an effective solution for continuous vital sign monitoring.